"I don't mean extradimensional in a woo-woo sense": Doing non-explanation in discussions of unidentified aerial phenomena. (January 2023) - McVittie, Chris; McKinlay, Andy
Abstract: In everyday talk, speakers commonly provide explanations that "make plain" or "make intelligible" prior talk. Little work, however, has examined talk in which speakers offer no explanation for what is being described. We consider talk about "unidentified aerial phenomena" (UAPs) from news media interviews. Interviewees distanced themselves from accountability for explaining UAPs or proposed multiple candidate explanations. Interviewers tabled their own potential explanations. Participants' talk did not "make plain" or "make intelligible" phenomena being discussed. These findings show that explanations are a participants' concern. These interactions allow discussion of topics of broad public interest, thereby "doing news". Highlights: In contrast to most everyday talk, there are instances where an absence of any explanation is a key element of descriptions. In news media interviews, individuals can avoid offering a single definitive explanation of social events. Interviewees can dodge responsibility, propose candidate options, or go along with an interviewer's explanation. This talk is not designed to "make plain" or "make intelligible" by explanation the phenomena that are being discussed. Such talk allows for further ongoing discussion of topics of interest to a broader public, that is it "does news".